Local effects of cryospheric change on agriculture and pasture in Nepal Trans Himalaya. - Paudel, Keshav Prasad (2011)
Keshav Prasad Paudel, University of Bergen, Norway / Nepal, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.